The Comic Strip Genre for English Language Teaching: An Interactionist Socio-Discursive Perspective - Espuri, Paulo Henrique; Rios-Registro, Eliane Segati (The ESPecialist, 2014)
The Basic Education Curriculum Guidelines (Paraná, 2008), a document which guides the educational sphere in the State of Paraná, recommend that students must be considered as social individuals in the process of teaching and learning. In view of this scenario, this study aims at presenting the potentialities of the work with the comic strip genre at school. Based on the didactic model proposed by Cristovão, Durão and Nascimento (2007), we developed a didactic sequence (Dolz, Noverraz, Schneuwly, 2004) having the webquest as a support. Our theoretical perspective is based on textual analysis (Bronkcart, 2009), as well as on the concept of language capacities (Dolz & Schneuwly, 2004). It is concluded that the comic strip genre is a powerful tool in EFL teaching.